Correcting for contact area changes in nanoindentation using surface acoustic waves. (February 2017) - Beck, Christian E.; Hofmann, Felix; Eliason, Jeffrey K.; Maznev, Alexei. A.; Nelson, Keith A; Armstrong, David E.J.
Abstract: Nanoindentation is extensively used to quantify nano-scale mechanical behaviour. A widely-used assumption is that a well-defined, material-independent relationship exists between the indentation depth and indenter contact area. Here we demonstrate that this assumption is violated by ion-implanted tungsten, where pileup around the indenter tip leads to substantial changes in contact area. Using high accuracy surface acoustic wave measurements of elastic modulus, we are able to correct for this effect. Importantly we demonstrate that a priori knowledge of elastic properties can be readily used to compensate for pileup effects in nanoindentation without the need for any further measurements. Graphical abstract: